Mixed Phenolic Acids Mediated Proliferation of Pathogens Talaromyces helicus and Kosakonia sacchari in Continuously Monocultured Radix pseudostellariae Rhizosphere Soil - Wu, Hongmiao; Wu, Linkun; Wang, Juanying; Zhu, Quan; Lin, Sheng; Xu, Jiahui; Zheng, Cailiang; Chen, Jun; Qin, Xianjin; Fang, Changxun; Zhang, Zhixing; Azeem, Saadia; et al. (Frontiers in Microbiology, 2016)
Radix pseudostellariae L. is a common and popular Chinese medication. However, continuous monoculture has increased its susceptibility to severe diseases. We identified two pathogenic microorganisms, Talaromyces helicus M. (KU355274) and Kosakonia sacchari W. (KU324465), and their antagonistic bacterium, Bacillus pumilus Z. in rhizosphere soil of continuously monocultured R. pseudostellariae. Nine types of phenolic acids were identified both in the rhizosphere soil and in culture medium under sterile conditions. A syringic acid and phenolic acid mixture significantly promoted the growth of T. helicus and K. sacchari. T. helicus could utilize eight types of phenolic acids, whereas K. sacchari could only use four phenolic acids. K. sacchari produced protocatechuic acid when consuming vanillin. Protocatechuic acid negatively affected the growth of B. pumilus. The 3A-DON toxin produced by T. helicus promoted the growth of K. sacchari and inhibited growth of B. pumilus at low concentrations. These data help explain why phenolic exudates mediate a microflora shift and structure disorder in the rhizosphere soil of continuously monocultured R. pseudostellariae and lead to increased replanting disease incidence.